Adrenergic Blockade by Nebivolol to Suppress Oral Squamous Cell Carcinoma Growth via Endoplasmic Reticulum Stress and Mitochondria Dysfunction - Chen, Qian; Jiang, Han; Wang, Zhen; Cai, Lu-Yao; Jiang, Yu-Chen; Xie, Liang; Zhou, Yu; Zeng, Xin; Ji, Ning; Shen, Ying-Qiang; Chen, Qian-Ming (Frontiers in Pharmacology, 2021)
Adrenergic nerve fibers in the tumor microenvironment (TME) promote tumor growth and represent as a potential target for cancer therapy. However, the effectiveness of targeting adrenergic nerve fibers for oral squamous cell carcinoma (OSCC) therapy need to be evaluated by preclinical data. Herein, the 4NQO-induced and orthotopic xenograft OSCC mice models were established. We demonstrated that the using 6OHDA chemical denervation as well as using nebivolol adrenergic blockade could halt the oral mucosa carcinogenesis. Our preclinical studies suggested that nebivolol, which is widely used to treat cardio-vascular diseases, can be repositioned as a potential candidate to treat OSCC. Remarkably, we revealed the precise effect and mechanism of nebivolol on OSCC cells proliferation, cell cycle and cell death. Administration of nebivolol could activate endoplasmic reticulum (ER) stress signaling pathway through increasing the expression of inducible nitric oxide synthase (iNOS), which subsequently trigger the integrated stress response (ISR) and cell growth arrest. Simultaneously, ER stress also induced mitochondrial dysfunction in OSCC cells. We found that the accumulation of dysfunctional mitochondria with the impaired electron transport chain (ETC) caused increasing ROS production, which ultimately resulted in OSCC cell death. Altogether, our finding suggested a novel therapeutic opportunity for OSCC by targeting adrenergic nerve fibers and repurposing nebivolol to treat OSCC can be represented as an effective strategy.